Analyzing E-Commerce Customer Loyalty Using The E-Service Quality Method - Sibara, Lisa; Sihombing, Denny Jean Cross (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2023)
Indonesia is a country of e-commerce service users that occupies the first globally. In Indonesia's increasingly fierce e-commerce competition, users are faced with various choices, so user loyalty in using one application is critical. Therefore, it is necessary to analyze user loyalty in e-commerce. This study measures customer loyalty to e-commerce, especially the Bukalapak application. This research uses a purposive sampling technique and an e-service quality measurement method. The results of this study are of the eight hypotheses proposed; there are five rejected hypotheses, namely the variables tangible, reliability, responsiveness, assurance, and fulfillment have no positive effect on satisfaction, and there are three accepted hypotheses, namely the variables privacy, compensation, and contact have a positive effect on satisfaction